2011
DOI: 10.1073/pnas.1102349108
|View full text |Cite|
|
Sign up to set email alerts
|

FGF2 gene transfer restores hippocampal functions in mouse models of Alzheimer's disease and has therapeutic implications for neurocognitive disorders

Abstract: The adult hippocampus plays a central role in memory formation, synaptic plasticity, and neurogenesis. The subgranular zone of the dentate gyrus contains neural progenitor cells with self-renewal and multilineage potency. Transgene expression of familial Alzheimer's disease-linked mutants of β-amyloid precursor protein (APP) and presenilin-1 leads to a significant inhibition of neurogenesis, which is potentially linked to age-dependent memory loss. To investigate the effect of neurogenesis on cognitive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 73 publications
6
103
2
Order By: Relevance
“…Indeed, the hippocampus is affected early in AD and memory impairment related to hippocampal damage is associated with the deregulation of neurogenesis [52]. The subventricular zone of the lateral ventricle and the subgranular layer of the dentate gyrus in the hippocampus are both associated with adult neurogenesis [16][17][18][19]. It has been proven that a dramatic decline in neurogenesis contributes to the impairment of learning and memory in AD models [20,53].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the hippocampus is affected early in AD and memory impairment related to hippocampal damage is associated with the deregulation of neurogenesis [52]. The subventricular zone of the lateral ventricle and the subgranular layer of the dentate gyrus in the hippocampus are both associated with adult neurogenesis [16][17][18][19]. It has been proven that a dramatic decline in neurogenesis contributes to the impairment of learning and memory in AD models [20,53].…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have provided strong evidence that the loss of hippocampal neurogenesis contributes to the development of AD and the impairment of learning and memory [16][17][18][19]. Several studies using a transgenic mouse model of AD have shown significant alterations in the process of adult neurogenesis in the hippocampus [20].…”
Section: Introductionmentioning
confidence: 98%
“…Basic fibroblast growth factor (FGF2) plays a key role in proliferation and differentiation of neuronal progenitors (36). We found approximately 70% reduction in Fgf2 messenger RNA (mRNA) levels in the DG of Ts65Dn mice, compared with 2N counterparts.…”
Section: Fibroblast Growth Factor Gene Expressionmentioning
confidence: 97%
“…bFGF has generated considerable excitement as a promising therapy for neurodegenerative diseases, including PD [11], Huntington's disease [40] and Alzheimer's disease [41]. bFGF appeared to be efficacious in two Phase II clinical trials for stroke, but failed in the large scale Phase III trial [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Primary hippocampal neurons were seeded into 96-well plates and treated with 6-OHDA (50, 100, 150, 200 and 400 μM) for 24 h with or without bFGF (10,20,40 and 80 ng/mL). After 24 h incubation, cell viability was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay.…”
Section: Viability Assaymentioning
confidence: 99%